Lack of Data or Lack of Weasels? The Likely Silent Extinction of Weasel Mustela nivalis (Carnivora: Mustelidae) in Spain - Ana B. Llorca; Francisco S. Tortosa; José Guerrero-Casado (Diversity, 2024)
Records from online biodiversity databases (including citizen science data) can play a crucial role in enhancing scientific knowledge about the abundance, distribution, and population trends of poorly studied species which are usually not properly monitored. This study aims to demonstrate the utility of data hosted in GBIF in detecting the likely decline of species common and widely distributed in the past, but whose conservation status is now uncertain, such as the weasel (Mustela nivalis) in Spain. To address this, we analyzed data on its presence in Spain from 2008 to 2022 available on GBIF.org, and compared it with the distribution data from the Atlas of Mammals of Spain published in 2007. The results indicate that: (i) data from GBIF.org reveal a moderate decline (negative trend) in the weasel population in Spain during the study period; (ii) the species has been recorded in a limited number of 10 × 10 km UTM-squares (Universal Transverse Mercator) within its distribution range as defined by the 2007 atlas; and (iii) there are large areas of Spain in which the species has not been detected in recent years. These findings highlight the concerning conservation status of this carnivorous species and underscore the value of data from open access platforms such as GBIF in identifying potential silent extinctions.